COMMUNICATION ON WASTE MANAGEMENT POLICY IN THE CITY OF BANDUNG (STUDY OF THE LEADERSHIP PERIOD OF DADA ROSADA, RIDWAN KAMIL AND ODDED M DANIAL) - Dhini Ardianti; Vera Hermawan; Azmi Herdiyanti M; Natasa Kumalasah P (Jurnal Ekonomi, 2023)
Toxic substances can be released into the environment through garbage. Various waste management strategies are being tested by the government. Waste management policies that prioritize public health, environmental sustainability, and resource recovery. Waste management strategies in Bandung have garnered competing evaluations: the government sees them as successful, but residents have a more negative view. This study aims to further study the waste management policies implemented in the city of Bandung during the reign of Mayor Dada Rosada, Ridwan Kamil, and Odded M Daniel. This study used descriptive qualitative method. The results of the study show that each mayor's leadership brings its own pattern of policy implementation, but in general the policy has continuity, such as the Flowering Green policy in the Dada Rosada era which was focused again on becoming a Garbage Free Area during Ridwan Kamil's leadership and was sharpened by the Kang PisMan Policy during the leadership of Oded M Danial/Yana Mulyana.